Hepatitis A in Spain: Evolution of hospitalization in the period 2000–2021 - Angela Domínguez; Núria Torner; Núria Soldevila; Carmen Varela; María Guerrero-Vadillo; Marina Peñuelas; Ana Avellón; Eva Borràs; Ana Martinez; Pedro Plans; Carles Pericas; Cristina Rius; et al. (PLoS ONE, 2025)
Background Hepatitis A is an acute disease of the liver caused by the hepatitis A virus (HAV). Chronic liver disease, other viral hepatitis coinfections, and age over 50 years are the main host factors associated with an increased risk of complications. We investigated the evolution of hepatitis A hospitalizations and in-hospital deaths during 2000–2021 in Spain according to demographic characteristics, presence of other sexually transmitted infections, and vaccination strategy (universal or risk-group vaccination). Methods Using data from the Spanish National Health System’s Minimum Basic Data Set, we calculated age-standardized cumulative hospitalization incidence and 95% confidence interval (CI), factors associated with hospital stay, and hospitalization deaths. Adjusted OR (aOR) values were calculated using a multivariate logistic regression model. Results The Spanish cumulative hospitalization incidence for hepatitis A over the 22-year period was 8.84 per 1 000 000 globally and 12.54 and 5.26 per 1 000 000 for men and women, respectively (RR = 2.38; 95% CI: 2.28–2.50). Median length of stay was 4 days (range 0−85). Factors associated with hospitalization >7 days were age groups 40−59 and ≥60 years (aOR 1.58; 95% CI: 1.37–1.82 and aOR 5.09; 95% CI: 4.01–6.47, respectively), cirrhosis (aOR 6.11; 95% CI: 2.59–14.43), and presence of HIV and HBV (aOR 1.65; 95% CI: 1.15–2.38 and 2.01; 95% CI: 1.03–3.63, respectively). In-hospital deaths were associated with age ≥ 60 years (aOR 35.23; 95% CI: 11.12–111.58), hospitalization >7 days (aOR 4.37; 95% CI: 1.80–10.58), cirrhosis (aOR 8.84; 95% CI: 2.37–32.99), and HCV infection (aOR 8.66; 95% CI: 1.57–47.87). The cumulative hospitalization incidence was lower in regions implementing universal vaccination (RR 0.79; 95% CI: 0.75–0.84). Conclusion Results of studies based on characteristics of hospitalized hepatitis A cases taking into account the existing prevention policies can be useful to have a better knowledge about its evolving epidemiology and to improve the prevention and control of the disease.